The presence of macrophages and inflammatory responses in an in vitro testicular co-culture model of male reproductive development enhance relevance to in vivo conditions. (October 2016) - Harris, Sean; Shubin, Sara Pacheco; Wegner, Susanna; Van Ness, Kirk; Green, Foad; Hong, Sung Woo; Faustman, Elaine M.
Abstract: Our 3-dimensional testis co-culture system (3D-TCS) represents a promising model of male reproductive toxicity which captures sensitive processes of male reproductive development and contains the main testes cell types (germ, Leydig and Sertoli cells). Macrophages are another cell type important for testicular function and help to modulate immuno-endocrine processes during testes development. Chemicals such as phthalate esters (PE's) affect macrophage function and testosterone production in the testes in vivo . The aim of this study was to determine whether macrophages were present in the 3D-TCS and investigate responses in our model that may be related to immuno-endocrine functions. We observed consistent expression of the resident macrophage marker ED2 as well as increases in inflammatory cytokines produced by macrophages and testes cells (IL-6, TNF-α and KC/GRO) after exposure to toxic PE's. Pathway analysis of gene expression changes after exposure to PE's showed that IL-6 and TNF-α signaling pathways were enriched after treatment with reproductively toxic, but not non-reproductively toxic phthalates. These results indicate that macrophages and inflammatory processes are captured in the 3D-TCS and that these processes are impacted by exposure to reproductive toxicants. These processes represent a major mode of action for in vivo testis toxicity for a variety of compounds and our novel in vitro model is able to capture toxicant perturbation of immune function. Highlights: The presence of macrophages and inflammatory cytokines were evaluated in an in vitro model of testis development. The marker protein ED2 was detected in culture, indicating the presence of resident macrophages. Levels of inflammatory cytokines were increased after exposure to phthalate esters in culture. Analysis of microarray data indicated that inflammatory pathways were activated by phthalate exposure. Results indicate that this testis model captures responses in inflammatory pathways similar to in vivo testis.